A review on solar dryers to evaluate the performance and drying characteristics for agricultural products - Jebaraj S.; Mohammed Yahaya Khan (Renewable Energy and Sustainable Development, 2025)
In this paper, an attempt has been made to review the various researches on drying agricultural products using solar radiation in a self-consistent means in the areas of performance analysis, energy, and exergy analysis, experimental investigation, and optimization of solar dryers. Various simulation models to estimate the thermal performance and drying characteristics of different types of solar collectors have been presented. Some of the recent developments in solar drying systems are presented. Further, it is found that the dryers are classified as integral type, distributed type, and mixed-mode. Previous research by different authors proved that the drying period of agricultural products was considerably decreased by solar drying. It is concluded that this paper will be very much supportive for the researchers, academicians, scientists, and policymakers in the area of solar dryers. It is also suggested that a standard test should be developed for solar drying systems.   Received: 30 September 2024 Accepted: 07 January 2025 Published: 19 January 2025